Analisis Pengaruh Kepemimpinan dan Kompetensi Guru terhadap Kinerja Guru - Sri Larasati (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2010)
Leadership, Competence, and Performance is a Component that effect each other, this is reinforced by Government REGULATION no. 24,2008, about teacher, article 2, of which it is said that teacher must have academic qualifications, competence, certifications becouse that study was conducted to determine the effect of leadership, competence, against the performance of teachers with reseach object SMK Pariwisata teachers Trisula with population sample of 20 teacher. Analyzing the Multiple Regression Analysis counducted and from the result obtained is known that the 2 hypothesis proposed are not proven true, becouse of the test together with the f test, showed that the leadership and competence to provide a very significant effect on performance with F count > F table (939,193> 1,73 ) and from the test individually with the t test result showed that Leadership provides a very significant influence, where t count > t table(4,754 > 2,09) and Competence have a significant influence where t count > t table (2,796 > 2,09), whereas the level of influence given leadership, competency determination against performance seen from the influence of R is 0,805 or 80,5%